Outlook for the dry bulk shipping market in the next 5 years - Yeo, Kai Hong (2016)
The main objective of this report is to provide an outlook of the dry bulk shipping market within the next 5 years. The market has been on a decline since the 2008 financial crisis, with shipowners that are struggling under the pressure of freight rates that are at an all-time low. The question that everyone is asking is when the market will finally recover from the current depression. Through this report, research is done on the key variables that influence the dry bulk shipping market, comprising of the world economy, demand for dry bulk commodity shipping, supply of dry bulk fleet and freight rates that reflect the current market situation. For the supply side, variables like fleet size, number of new orders and scrapping are analysed in order to determine the trend of the dry bulk fleet development. For the demand side, trade levels and market activities for the 3 main dry bulk commodity are analysed to obtain a read on the global demand for dry bulk. Despite the global economy on a path of recovery, the situation in the dry bulk market depicts a different picture. The BDI is at a historical low, due to the severe oversupply problem in the dry bulk fleet. With demand levels of dry bulk shipping flatting out and possibly waning, the effects of increased scrapping of vessels and reduction of new orders are minimized. The dry bulk market is unlikely to show any clear signs of recovery, not until the oversupply problem is resolved and demand of shipping to catch up with supply of vessels. The resolution of this depression is not expected to happen anytime in the near future.